Health-related quality of life after treatment for neoplasia of the major salivary glands: a pilot study. Issue 7 (September 2016) - Breeze, J.; Morrison, A.; Dawson, D.; Tipper, J.; Rehman, K.; Grew, N.; Pigadas, N.
Abstract: Treatment of malignancy of the salivary glands risks damage to the cranial nerves, and clinicians' traditional view has been that this will result in adverse effects on physical function and subsequent health-related quality of life (QoL). Preservation of nerves has been advocated to lessen this impact, but we know of no evidence that sacrifice of the facial nerve has any effect on subsequent QoL. We collected data prospectively before and after operation for all malignancies of the major salivary glands treated over five years using two health-related QoL questionnaires: the University of Washington Quality of Life Questionnaire and the Patient Concerns Inventory. Fifteen of17 eligible patients fulfilled the inclusion criteria by having assessments completed both before and after operation. Scores for QoL after treatment of cancer of the submandibular gland dropped at six months, but had resolved to more than 80% of the pretreatment score by a year, with the exception of the domains taste and saliva. The four patients who had weakness of the facial nerve after treatment had appreciable reductions in the physical function components of the QoL domains, but no significant reduction in the social-emotional domains. Use of the Patient Concerns Inventory enables tailoring of services towards those clinicians who a patient feels are potentially most likely to help alleviate factors that have an adverse effect on QoL. Sacrifice of the facial nerve in malignant parotid gland disease results in a considerable reduction in functional health-related QoL scores. Methods to ensure clearance of the tumour while limiting the effects on facial nerve function should always be considered.